Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1175/2011bams2928.1
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Economic Sensitivity to Weather Variability

Abstract: To estimate the economic effects of weather variability in the United States, the authors define and measure weather sensitivity as the variability in economic output that is attributable to weather variability, accounting for changes in technology and changes in levels of economic inputs (i.e., capital, labor, and energy). Using 24 yr of economic data and weather observations, quantitative models of the relationship between state-level sectoral economic output and weather variability are developed for the 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(74 citation statements)
references
References 6 publications
1
67
0
2
Order By: Relevance
“…These time-scales range from short range (1-5 days), to medium range (7-15 days), and long range (3-12 months) (Robertson and Wang, 2012;Vitart et al, 2014;Lawal, 2015). For the past several decades, forecasts of weather, ocean and other environmental phenomena made on short and medium range time-scales have yielded invaluable information to improve decision making across many socioeconomic sectors (Lazo et al, 2011). Yet, there are some fundamental problems that limit the use of these forecasts.…”
Section: Introductionmentioning
confidence: 99%
“…These time-scales range from short range (1-5 days), to medium range (7-15 days), and long range (3-12 months) (Robertson and Wang, 2012;Vitart et al, 2014;Lawal, 2015). For the past several decades, forecasts of weather, ocean and other environmental phenomena made on short and medium range time-scales have yielded invaluable information to improve decision making across many socioeconomic sectors (Lazo et al, 2011). Yet, there are some fundamental problems that limit the use of these forecasts.…”
Section: Introductionmentioning
confidence: 99%
“…Lazo et al (2011) confirmed it to be the second most weather sensitive sector of the US economy, following mining, with 12.1% of output being exposed to weather. Within the EU project "Weather Impacts on Natural, Social and Economic Systems -WISE", the impact of weather on agriculture has been studied in the United Kingdom (Subak et al 2000), Netherlands (Tol 2000), Germany (Flechsig et al 2000) and Italy (Galeotti et al 2004).…”
Section: Weather Impact On Agricultural Productionmentioning
confidence: 93%
“…If the volatility of output of a certain sector is caused by the changes in weather, the sector is said to be weather sensitive. Studies show that weather sensitivity varies between the economic sectors and geographical areas and that all economic sectors are to some extent weather sensitive (Larsen 2006, Lazo et al 2011.…”
Section: Doi: 1017221/188/2015-agriceconmentioning
confidence: 99%
“…Nowadays, the accurate weather information is demand due to the strong influence of the weather condition to social and economic activities (Lazo et al, 2011). The information is not only used in weather alert for safety reason, but the more important is for long-term planning such as Southwest Monsoon (SWM) from the end of May to September and the Northeast Monsoon (NEM) from November to March.…”
Section: Introductionmentioning
confidence: 99%